2011
DOI: 10.1016/j.actpsy.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of interletter spacing in visual-word recognition

Abstract: Despite the importance of determining the effects of interletter spacing on visual-word recognition, this issue has often been neglected in the literature. The goal of the present study is to shed some light on this topic. The rationale is that a thin increase in interletter spacing, as in c a s i n o, may reduce lateral interference among internal letters without destroying a word's integrity and/or allow a more precise encoding of a word's letter positions. Here we examined whether identification times for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 45 publications
7
55
2
Order By: Relevance
“…First, these results reconfirm that subtle low-level font characteristics do influence eye movement behavior during reading Rayner, Slattery, & Bélanger, 2010;. We found that wider spacing results in shorter average fixation durations, consistent with the linear facilitative effects reported by Perea et al (2010) and Perea and Gomez (2012) using the lexical decision task. While not statistically significant with regard tothe other spacing conditions, gaze durations on target words presented in Times New Roman were shortest in the +1/2 pixel condition, which also agrees with Perea et al and Perea and Gomez.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…First, these results reconfirm that subtle low-level font characteristics do influence eye movement behavior during reading Rayner, Slattery, & Bélanger, 2010;. We found that wider spacing results in shorter average fixation durations, consistent with the linear facilitative effects reported by Perea et al (2010) and Perea and Gomez (2012) using the lexical decision task. While not statistically significant with regard tothe other spacing conditions, gaze durations on target words presented in Times New Roman were shortest in the +1/2 pixel condition, which also agrees with Perea et al and Perea and Gomez.…”
Section: Discussionsupporting
confidence: 77%
“…There are reports of facilitation in lexical decision tasks with subtle increases to intraword space (Perea & Gomez, 2012). However, as Perea, Moret-Tatay, and Gomez (2010) noted, the results of studies that use subtle manipulations of increased intraword spacing are somewhat inconsistent, probably due to the fact that the amount of space added between letters varied across the studies, as did the fonts used in the studies. Fonts can differ quite a bit in their default intraword spacing.…”
Section: Intraword Spacing Effectsmentioning
confidence: 65%
See 2 more Smart Citations
“…Perea, et al (2011), examined the impact that a slight increase of inter-letter spacing had on Spanish word recognition in the lexical decision task (LDT). They used the Times New Roman font with either default spacing or a small amount additional spacing (+1.2 pts).…”
Section: Small Letter-spacing Manipulationsmentioning
confidence: 99%